2003
DOI: 10.1159/000070723
|View full text |Cite
|
Sign up to set email alerts
|

Langage oral et écrit chez des enfants prématurés: résultats à 7½ ans

Abstract: La prématurité induit des facteurs de risques de retard cognitif, particulièrement de retard dans le langage oral et écrit. Ces facteurs de risques peuvent être liés aux variables physiologiques et/ou environnementales. Cette étude a deux objectifs: (1) repérer quels sont les enfants prématurés les plus à risque de retard cognitif et de langage oral et écrit et (2) estimer l’intérêt d’un bilan précoce de langage oral proposé dès 3½ ans à ces enfants en mesurant sa prédictivité sur l’apprentissage de la lecture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…(13, 23, 24) Hearing is essential to language development and there is evidence that peripheral auditory dysfunction or auditory sensory deprivation during the critical period of development may affect central auditory function and later language development. (1012, 25) Children with hearing loss and/or auditory neuropathy may demonstrate language problems depending on the timing, degree, and duration of associated auditory dysfunction or auditory sensory deprivation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(13, 23, 24) Hearing is essential to language development and there is evidence that peripheral auditory dysfunction or auditory sensory deprivation during the critical period of development may affect central auditory function and later language development. (1012, 25) Children with hearing loss and/or auditory neuropathy may demonstrate language problems depending on the timing, degree, and duration of associated auditory dysfunction or auditory sensory deprivation.…”
Section: Discussionmentioning
confidence: 99%
“…(13) The reasons for this are not well understood, but auditory development is known to be intricately related to language development. (49) Auditory sensory deprivation during critical period of development has been demonstrated to lead to central auditory processing and language problems.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have pointed out the role of oral language in relation to literacy. In fact, in the study by Crunelle et al , about one‐third of preterm children at risk for lexicon and grammar at 3.5 years showed delays on reading at 7 years.…”
Section: School Achievements: Reading Spelling and Mathematicsmentioning
confidence: 98%
“…A longitudinal study has shown that preterms at risk for lexical and grammatical problems in the first years of life had several delays (34%) on reading at age 7; 0 (Crunelle et al, 2003). Notwithstanding the relevance of this field of research, relationships between language and literacy have not been investigated in at-risk populations, such as preterm children, except for two studies.…”
Section: Relationships Between Language and Literacymentioning
confidence: 99%
“…Although not completely concordant in their results, these studies revealed that the preterm population in general did not differ from full-term children in lexical production, but some difficulties characterised preterms with greater immaturity (birthweight f1000 grams or gestational age f32 weeks). Preterms have been found to have a shorter mean length of utterance (MLU) at age 2 ; 6 (in preterms with greater immaturity ; Sansavini et al, 2006), at age 3 ; 6 (Sansavini, Guarini, Alessandroni, Faldella, Giovanelli & Salvioli, 2007) and at age 5 ; 0 (Crunelle, Le Normand & Delfosse, 2003). The results found in the first years of life and until school age highlighted how preterm birth may similarly affect lexical development across different languages.…”
Section: Introductionmentioning
confidence: 99%